Morning glory species co-occurrence is associated with asymmetrically decreased and cascading reproductive isolation - Ostevik, Kate; Rifkin, Joanna; Xia, Hanhan; Rausher, Mark (Dryad, 2020)
Hybridization between species can affect the strength of the reproductive
barriers that separate those species. Two extensions of this effect are:
(1) the expectation that asymmetric hybridization or gene flow will have
asymmetric effects on reproductive barrier strength and (2) the
expectation that local hybridization will affect only local reproductive
barrier strength and could therefore alter within-species compatibility.
We tested these hypotheses in a pair of morning glory species that exhibit
asymmetric gene flow from highly selfing Ipomoea lacunosa into
mixed-mating I. cordatotriloba in regions where they co-occur. Because of
the direction of this gene flow, we predicted that reproductive barrier
strength would be more strongly affected in I. cordatotriloba than I.
lacunosa. We also predicted that changes to reproductive barriers in
sympatric I. cordatotriloba populations would affect compatibility with
allopatric populations of that species.  We tested these
predictions by measuring the strength of a reproductive barrier to seed
set across the species’ ranges. Consistent with our first prediction, we
found that sympatric and allopatric I. lacunosa produce the same number of
seeds in crosses with I. cordatotriloba, whereas crosses between sympatric
I. cordatotriloba and I. lacunosa are more successful than crosses between
allopatric I. cordatotriloba and I. lacunosa. This difference in
compatibility appears to reflect an asymmetric decrease in the strength of
the barrier to seed set in sympatric I. cordatotriloba, which could be
caused by I. lacunosa alleles that have introgressed into I.
cordatotriloba. We further demonstrated that changes to sympatric I.
cordatotriloba have decreased its ability to produce seeds with allopatric
populations of the same species, in line with our second prediction. Thus,
in a manner analogous to cascade reinforcement, we suggest that
introgression associated with hybridization not only influences
between-species isolation but can also contribute to isolation within a
species.
These data were generated by growing morning glory plants from multiple
populations of two species in a common environment and making crosses
between the individuals (see Ostevik et al. 2020 for details). We recorded
whether crosses produced a fruit. In cases where a fruit was produced, we
further recorded the weight of the fruit, the number of seeds inside the
fruit, and the weight of those seeds. The data have been lightly filtered
to remove unreliable crosses (e.g., cases in which the plant died between
pollination and fruit set and cases in which the flower was damaged in
some way).
Keywords: FOS: Biological sciences